2022
DOI: 10.1021/acsomega.1c06003
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization Spectroscopic and Theoretical Study on the Molecular Structures of cis- and trans-3-Chlorothioanisole

Abstract: Resonance-enhanced two-photon ionization (R2PI) and massanalyzed threshold ionization (MATI) spectra are measured for the cis-and trans-3-chlorothioanisole (3ClTA). The first electronic excitation energy (E 1 ) and the adiabatic ionization energy (IE) of the cis-rotamer are determined to be 33 959±3 and 65 326±5 cm −1 , respectively, and those of the trans-rotamer are determined to be 34102±3 and 65 471±5 cm −1 , respectively. Density functional theory (DFT) calculations confirm that both the cis-and trans-rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…They are consistent with the 1C-R2PI spectroscopic measurement (Figure ) that the trans -0 0 0 band is slightly stronger than that of the trans -torsion mode τ 0 1 at 44 cm –1 . This is similar to the case of 3ClTA, for which both theoretical calculations and spectroscopic measurements confirmed its planarity in the S 1 state . The 0 + band is the most prominent peak in the MATI spectrum of trans -3FTA via the 0 0 0 level, as shown in Figure a.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…They are consistent with the 1C-R2PI spectroscopic measurement (Figure ) that the trans -0 0 0 band is slightly stronger than that of the trans -torsion mode τ 0 1 at 44 cm –1 . This is similar to the case of 3ClTA, for which both theoretical calculations and spectroscopic measurements confirmed its planarity in the S 1 state . The 0 + band is the most prominent peak in the MATI spectrum of trans -3FTA via the 0 0 0 level, as shown in Figure a.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to the −SCH 3 group, the substitution effect of the F atom may also contribute. Our previous study showed that the torsion vibrational peaks of both cis - and trans -3ClTA in the R2PI spectra were much weaker than that of the 0 0 0 bands . The electron-withdrawing effect of the F atom predominates over the electron-donating effect, which increases instead of neutralizing the positive hole on the benzene ring .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations